Development of Mathematics Learning Tools Using Peer Instruction with Structured Inquiry Method Based on Local Culture Oriented on Mathematical Problem-Solving Ability - Ruswana, Angra Meta; Zamnah, Lala Nailah; Shahid , Mursaleen; Umar, Nasir (EDUPEDIA Publisher, 2023)
This research aims to describe the characteristics of mathematics learning tools and produce valid, practical and effective mathematics learning tools using the Peer Instruction with Structured Inquiry (PISI) method based on local culture which is oriented towards mathematical problem solving abilities. This research is development research using the ADDIE development model. Data analysis was carried out in this research to determine the feasibility of the development product in terms of the validity, practicality and effectiveness of the learning tools being developed. The research results show that 1. mathematics learning tools using the PISI method based on local culture oriented towards mathematical problem solving abilities have several characteristics, namely: a) Learning activities carried out using the PISI method stage consist of 2 parts, namely Peer Instruction which indirectly leads to the Structured Inquiry stage; b) The problem investigated in learning is a problem with the local cultural context of Ciamis; c) The use of local cultural context makes the mathematical knowledge concepts obtained by students become more meaningful and students become aware of the importance of mathematics because mathematical concepts are also found in students' daily activities; d) The instrument used in assessing learning outcomes is in the form of mathematical problem solving ability test questions. 2. Mathematics learning tools using the PISI method based on local culture are oriented towards mathematical problem solving abilities that meet the criteria of being valid, practical and effective.